Ocular cranial nerve palsies secondary to sphenoid sinusitis - Aiman El Mograbi; Ethan Soudry (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2017)
Objective: The clinical presentation of sphenoid sinusitis can be highly variable. Rarely, sphenoid sinusitis may present with cranial nerve complications due to the proximity of these structures to the sphenoid sinus. Method: A case series from Rabin Medical Center and all cases of cranial nerves palsies secondary to sphenoid sinusitis that have been reported in the literature were reviewed. Results: Seventeen patients were identified. The abducent nerve was the most common cranial nerve affected (76%), followed by the oculomotor nerve (18%). One patient had combined oculomotor, trochlear and abducent palsies. The most common pathology was isolated purulent sphenoid sinusitis in 64% followed by allergic fungal sinusitis (AFS) in 18%, and fungal infection in 18%. 94% had an acute presentation. The majority (85%) received a combined intravenous antibiotics and surgical treatment. The remainder received conservative treatment alone. Complete recovery of cranial nerve palsy was noted in 82% during follow up. Conclusion: Sphenoid sinusitis presenting as diplopia and headaches is rare. A neoplastic process must be ruled out and early surgical intervention with intravenous antimicrobial therapy carry an excellent outcome with complete resolution of symptoms. Keywords: Sphenoid, Sinusitis, Sphenoiditis, Ocular, Cranial nerve, Palsy